Narratives of Abd Al-Rahman bin Harmala in the Nine Books (Chapter on Naming when Ablution, as an Example ) - An Analytical Study - (Islamic Sciences Journal, 2023)
ABSTRACT                                     There is no doubt that the science of the Prophet’s hadith is one of the highest and most beneficial sciences. Allah Almighty has guided me to write this science , so my choice fell on one of its topics, which is (The Narratives of Abd Al-Rahman bin Harmala in the Nine Books – An Analytical Study -) .After researching the nine books and what the authors of these books brought out for him we found that Abd Al-Rahman bin Harmala had forty-five narrations, and after deleting the repeated ones, we found them to be twenty-one narrations. We will put them in your hands, divided according to the  jurisprudential chapters .We do not find any thing that enables us to identify the date of the narrators birth who is Abd Al-Rahman bin Harmala. However, one can that from the peers who lived with him, and through the sheikhs from whom Abd Al-Rahman bin Harmala was taken so, his birth may have been between 60 AH to 70 AH. Allah  knows.
Keywords: Abd Al-Rahman ibn Harmala, his death, some of those who narrated from them, some of those who narrated from him, the name of Allah when performing ablution, the chain of transmission.